Anesthetic management of caesarean section in a patient with double outlet right ventricle - Rohith Krishna; Umesh Goneppanavar (Wolters Kluwer Medknow Publications, 2012)
Double outlet right ventricle (DORV) is a rare congenital heart defect involving the great arteries. In DORV, both aorta and pulmonary artery arise from the right ventricle resulting in admixture of blood. We report a 22-year-old parturient with DORV and severe pulmonary stenosis who underwent caesarean delivery at 36 weeks gestation with low dose combined spinal-epidural anesthesia. This lady was assessed by echocardiogram to have situs inversus, dextrocardia, severe pulmonary artery stenosis (gradient = 146 mm Hg), DORV with subarterial VSD (1 cm). She had 95% room air saturation and her blood investigations were within normal limits. We established a peripheral venous access and radial arterial line for continuous blood pressure monitoring. Combined spinal epidural anesthesia was considered a better option. Epidural catheter was secured at L 2 -L 3 space and fixed after giving test dose 3 mL 2% lignocaine. Subarachnoid block administered at L 3 -L 4 level using 1.2 mL of 0.5% heavy bupivacaine. A sensory block of T 10 was obtained which was supplemented with 4 mL 0.75% ropivacaine to obtain a level of T 6 . Patient tolerated the procedure well. She was shifted to post-operative ICU. Post-operative pain was managed with epidural 0.2% ropivacaine at 4 mL/h. Patient remained hemodynamically stable throughout the procedure and in the postoperative period while she was being followed up for subsequent 48 h.